Chinua Achebe's Appropriation of Du Bois's Of the Coming Of John - Walid MESSAOUDI, Ahmed Seif Eddine NEFNOUF, Boubaker MOHREM, Noureddine DERKI & Otmane Abdelkader DRISSI (Akofena, 2024)
Abstract: This paper examines the African critic and novelist Chinua Achebe's reworking and recycling W.E.B.DU Bois's short story "Of The Coming Of John"(1903). Achebe's "Dead Men's Path"(1953) represents the return of the protagonist Michael Obi from his academic journey towards his home of origin Nigeria. He goes back to fulfill a mission of ruling a secondary school that suffers backwardness. To some extent, Achebe by doing so, is appropriating and adapting W.E.B.DU Bois's short story "Of The Coming of John" (1903) that exposes the dilemma of double consciousness in USA as well as the issues of race, ethnicity and discrimination. In Du Bois's work there are two characters possessing the same name of John, but they are completely different in term of social class and skin color. Thus, this research is both analytic and comparative; relying on a close reading of the two works to distinguish both the similarities and the differences between them. Also, it aims at shedding lights on how Achebe recreates the American atmosphere and the problem of north-south in the United States and molds it in Nigeria's decolonization mood, as well as, the debate between modernism and tradition.